Avaliação do potencial de captura de CO2 em pastas de cimento com adição de cal hidratada e da resistência à corrosão da armadura com aços CA-50 e microcompósito - Menegussi, Giovanna Costella (Universidade do Vale do Rio dos Sinos, 2024)
The cement industry is responsible for approximately 25% of industrial carbon dioxide emissions into the atmosphere, equivalent to, approximately, 7% of global CO2 emissions. Given the need to contain the increase in Earth's temperature, collective involvement in minimizing CO2 emissions into the atmosphere is essential. Given this, the capture and storage of carbon in concrete structures through carbonation has been gaining significant prominence. However, the advance of CO2 in cementitious compounds containing metal bars culminates in the corrosion process of the reinforcements. Thus, this research evaluated the potential for CO2 capture in cementitious masses by adding hydrated heat by X-ray diffraction and thermogravimetry tests. Furthermore, the physical and mechanical properties of the masses were studied by specificity resistance and porosity tests by nitrogen adsorption. To enable carbon sequestration, the resistance to carbonation corrosion of the steel microcomposite was investigated using corrosion potential and linear polarization resistance tests. The results indicated strong carbonation of C-S-H in the REF paste, which resulted in greater carbon capture, but with significant losses in mechanical strength. Adding hydrated lime increased the CO2 capture potential and minimized the carbonation of C-S-H in the masses, thus avoiding losses in mechanical strength – especially in the 2CH paste, which obtained an increase of approximately 23% in resistance to variations after carbonation. However, the masses with lime did not reach the CO2 capture potential in the investigated time, due to the decrease in the carbonation rate due to the increase in the alkaline reserve and densification of the cementitious matrix. In the corrosion analysis, the microcomposite steel (MC) was more resistant than the conventional carbon steel (CA-50), remaining passivated in all the investigated scenarios, especially after carbonation. Therefore, it was concluded that the hydrated lime publications preserved the C-S-H of the carbonation and that the use of MC steel avoided the corrosion process of the reinforcements, to enable the capture and storage of CO2 in structures, including reinforced concrete, without compromising durability and service life.
Keywords: Captura de carbono; Carbonatação; Hidróxido de cálcio; Corrosão; Aço microcompósito; Carbon capture; Carbonation; Calcium hydroxide; Corrosion; Microcomposite steel; ACCNPQ::Engenharias::Engenharia Civil